Benefit of using al-wadiah contract (saving instrument) in gold transactions - Shuib, Mohd Sollehudin; Osman, Amirul Faiz; Hashim, Hydzulkifli; Fadzil, Aiman (2016)
Gold trading and transactions nowadays involved more people and various background.However, according to Islamic business contract, gold is categorized under a special law of transaction items and it must follows a specific law of Islamic business transaction.This article focuses on how wadiah concepts can be applied in the contemporary gold trading and their benefit. The legality of the wadiah concepts is utmost important to be verified before its implementation.The aims of this article is to substantiate the concepts of wadiah in contemporary gold trading based on the main sources of Islamic law transactions.The finding shows that the wadiah concept is permissible in Islam.Furthermore, the wadiah also play important role in contemporary gold trading.Hence, wadiah contract can helps to resolve the gold trading issues where the physical assets of gold are distance from the buyer.